Ultrasonic testing of weldment - Chandrasekaran, P. V. N. (2008)
This project applies the Ultrasonic Testing method of NDT to detect the defects in weld specimens. For that it was aimed to produce weld specimens with buried defects in order to inspect and evaluate them using Ultrasonic testing (A-Scan method).